Position statement on the use of albumin in liver cirrhosis - Castro Narro, Graciela; Moctezuma Velázquez, Carlos; Male Velázquez, Rene; Trejo Estrada, Rafael; Bosques Padilla, Francisco Javier; Moreno Alcántar, Rosalba; Rodríguez Hernández, Heriberto; Bautista Santos, Aleida; Cortez Hernández, Carlos Alejandro; Cerda Reyes, Eira; Pérez Escobar, Juanita; Aldana Ledesma, Juan Manuel; et al. (2022)
Cirrhosis is characterized by a prolonged asymptomatic period in which the inflammation persists, increasing as the disease progresses. Proinflammatory cytokines and pro-oxidant molecules are key in the development of organ dysfunction. Cirrhosis progression and worsening of portal hypertension bring about bacterial translocation and systemic dissemination via portal circulation of bacterial products, and molecular patterns associated with damage, which exacerbate the systemic Inflammation. Albumin is a molecule that undergoes structural and functional changes as liver damage progresses, affecting its antioxidant, immunomodulatory, oncotic, and endothelial stabilizing properties. Our knowledge of the properties of albumin reveals a molecule with multiple treatment options, capable of targeting several physiopathological aspects of cirrhosis. For the elaboration of the present manuscript on the uses of albumin in liver cirrhosis, several experts in the field of hepatology in Mexico were divided into 5 working groups to summarise and formulate, when appropriate, position statements: 1)pathophysiology of cirrhosis and properties of albumin; 2)proven uses of albumin [large-volume paracentesis, spontaneous bacterial peritonitis (SBP), hepatorenal syndrome (HRS)]; 3)controversial/emerging uses of albumin (long-term use, acute decompensation, liver transplant, non-HRS kidney injury, muscle cramps, non-SBP infections, hyponatremia, encephalopathy); 4)use of albumin in acute-on-chronic liver failure, immunomodulation, and systemic Inflammation; 5)pharmacoeconomics.